2015
DOI: 10.1177/0271121414565911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Observational Methods and Their Relation to Ratings of Engagement in Young Children

Abstract: Although, collectively, results of earlier direct observation studies suggest momentary time sampling (MTS) may offer certain technical advantages over whole-interval (WIR) and partial-interval (PIR) recording, no study has compared these methods for measuring engagement in young children in naturalistic environments. This study compared direct observations of child engagement using WIR, PIR, and MTS methods to continuous duration recording (CDR), using measurement error, correlations, and inter-observer agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 32 publications
3
28
1
Order By: Relevance
“…The differences were notable in that higher estimates of duration of engagement and lower estimates of duration of problem behavior were obtained in CI activities when compared with TD activities consistently across all children. This study also supports previous research (Devine et al, 2011;Mann et al, 1991;Wood et al, 2015) that found PIR consistently overestimates occurrences of behavior, whereas MTS produces estimates closer to CR. Moreover, this study supports the conclusions of the Wood et al (2015) study that MTS might be a viable option for obtaining estimates of engagement and problem behaviors in early childhood settings.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The differences were notable in that higher estimates of duration of engagement and lower estimates of duration of problem behavior were obtained in CI activities when compared with TD activities consistently across all children. This study also supports previous research (Devine et al, 2011;Mann et al, 1991;Wood et al, 2015) that found PIR consistently overestimates occurrences of behavior, whereas MTS produces estimates closer to CR. Moreover, this study supports the conclusions of the Wood et al (2015) study that MTS might be a viable option for obtaining estimates of engagement and problem behaviors in early childhood settings.…”
Section: Resultssupporting
confidence: 90%
“…The observation method chosen should consider the dimensions (e.g., frequency or duration) of the behavior being measured to ensure the sample obtained represents an estimate that is "true" to the actual occurrence of the behavior (Lewis et al, 2014). In addition, researchers and practitioners may need to consider the practicality of different observation methods to ensure that the method is feasible given the context (Wood, Hojnoski, Laracy, & Olson, 2015).…”
Section: Use Of Direct Behavioral Observation To Measure Child Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study used classroom observations collected as part of a larger validation project for the BOSS-EE (Hojnoski et al, 2014). Recruitment procedures, study participants, and setting were previously described in Wood et al (2016).…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Recently, scholars have begun to examine potential behavioral progress monitoring tools that can be tailored to individual behaviors and interventions at Tiers 2 and 3. These include SDO measures such as momentary time sampling of academic engagement, as well as direct behavior ratings (DBRs) of engagement and disruption, both of which have evidence of reliability (Chafouleas et al, 2010; Wood, Hojnoski, Laracy, & Olson, 2016). The National Center on Intensive Intervention (NCII; www.intensiveintervention.org) offers a critical analysis of these various tools, including information on the technical adequacy (e.g., reliability, validity, sensitivity to change) and social validity (e.g., acceptability, feasibility, contextual fit).…”
Section: Data-based Decision Making For Social-behavioral Interventionsmentioning
confidence: 99%